2004
DOI: 10.1007/s11748-004-0128-6
|View full text |Cite
|
Sign up to set email alerts
|

Minimal access surgery for the repair of simple congenital heart defects

Abstract: Our experience demonstrated that minimal access surgery of the simple congenital heart defects provided excellent cosmetic results. Retention of pericardial effusion, possibly due to pericarditis, was a major risk factor of the prolonged hospital stay. The pericardio-pleural fenestration could reduce the risk of retention of effusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Wereported 262±124.40 ml blood loss during the first 24 hours post operatively in RAT group with no cases needed re-exploration for bleeding compared to only one patient in sternotomy group. Other studies showed 140 ± 57 mL [14] . In a similar study done by Narihiro I et al, comparing RAT with sternotomy, showed the same results in 21 patients included in the study.…”
Section: Blood Loss and Need Of Transfusionmentioning
confidence: 82%
See 1 more Smart Citation
“…Wereported 262±124.40 ml blood loss during the first 24 hours post operatively in RAT group with no cases needed re-exploration for bleeding compared to only one patient in sternotomy group. Other studies showed 140 ± 57 mL [14] . In a similar study done by Narihiro I et al, comparing RAT with sternotomy, showed the same results in 21 patients included in the study.…”
Section: Blood Loss and Need Of Transfusionmentioning
confidence: 82%
“…Demographic data of our study showed that 64% of patients were females with mean age 28.8±6.17 years, with a scar post operatively of 7-8 cm hidden under the breast which gave them an excellent cosmetic appearance and patient satisfaction. Many centers started to use the minimal invasive technique for closure of ASD with good outcome and efficiency same as median sternotomy with better patient satisfaction and pleasing cosmetic scar appearance [12][13][14] .…”
Section: Cosmetic Effectsmentioning
confidence: 99%
“…In the last two decades, mini-invasive closure of ASD has become a preferred procedure with equally good surgical results and better cosmetic results [ 14 - 16 ] compared to midline sternotomy. At our institute, all ASD patients were operated through right anterior minithoracotomy with peripheral CPB in adults and central cannulation in small children (10 kg).…”
Section: Discussionmentioning
confidence: 99%